Repercussões das políticas de turismo no Rio Grande do Norte, Brasil: o case de São Miguel do Gostoso - Taveira, Marcelo da Silva (2016)
This article addresses the impact of the main tourism policies implemented in Rio Grande do Norte (Brazil) in past decades, more precisely, from the 1930s to the present day. The central objective of this discussion is to promote theoretical and methodological debate on the effects of public policies for the Natal coastline, particularly in the municipality São Miguel do Gostoso, a beach and adventure tourism destination that is a major recreational hub for the practice of sailing and nautical sports, especially windsurfing and kitesurfing. Bibliographical and documentary research resulted in the chronological construction of the effectiveness of public policies that have had a direct impact on the structure and organization of the natal coastal territory, especially in São Miguel do Gostoso. The results show that the policies were decisive, and formed the basis of investments for the development of this territory for tourism and leisure